PENGARUH LATIHAN WEIGHT TRAINING TERHADAP PENINGKATAN KEMAMPUAN SHOOTING ATLET PETANQUE PELATDA NTB - Afdatul Rizki; Maulidin; Jamaludin (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2025)
This study aims to analyze the effect of weight training on improving the shooting ability of petanque athletes in the West Nusa Tenggara regional training center (Pelatda) in 2024. The study employed a pre-experimental one group pre-test post-test design with a sample of nine athletes selected using total sampling technique. The research instrument was the petanque shooting precision test (Souef, 2015). Data were analyzed using the Shapiro-Wilk normality test and Paired Sample T-Test. The results showed a significant improvement in athletes’ shooting ability after undergoing a weight training program. The mean shooting score increased from 15.00 in the pre-test to 28.55 in the post-test, with an improvement of 13.56 points (p < 0.05). These findings confirm that weight training contributes positively to muscle strengthening, motor coordination, and movement accuracy that support shooting skills. Therefore, integrating weight training into athlete development programs can be considered an effective strategy to enhance petanque performance at the national competition level.